The 24 h urinary Cortisol/Cortisone ratio and Epinephrine/Norepinephrine ratio for monitoring training in young female tennis players - Rouveix, M.; Duclos, M.; Gouarne, C.; Beauvieux, M. C.; Filaire, E. (International Journal of Sports Medicine, 2006)
The effect of training variations on the 24 h urinary cortisol/cortisone (C/Cn) ratio and the epinephrine/norepinephrine (E/NE) ratio in relation with mood (evaluated using the Brunel Mood Scale: BRUMS) and performance was investigated in seven trained young female tennis players (12.8 ± 1.7 years). Like the proposed model in adults, the monitoring of hormonal and mood parameters could be a useful index in training follow-up in young sportswomen. Assessment of nutritional intake, nitrogen excretion rate and nitrogen balance were also determined to measure the dietary practice of these athletes. Nitrogen balance was calculated from the mean daily protein intake and the urinary nitrogen excretion. Data were collected after a 1-month rest (September, T1), 3 months after T1 (after technical and endurance training: December, T2) and 7 months after T1 (after 4 months of increasing-volume/high-intensity training: March, T3). A significant increase in C/Cn ratio (+ 30 %, p < 0.05) were noted from T1 to T3. In the same time, urinary NE concentrations decreased significantly. The E/NE ratio increased from T1 to T2 and decreased at T3 (T1 vs. T3: - 30 %, p < 0.05). The BRUMS inventory at T3 reflected changes in specific mood states with a significant increase in fatigue and anger scores, while vigor scores decreased significantly compared to T1. This period also corresponded with the lowest percentage of matches won and with the highest training load. Energy intake was about 16 % lower than the French recommendations for girls of the same age. However, a positive nitrogen balance was observed from a mean intake of 1.0 g · kg-1 · day-1. Our results reveal that an increase of overnight urinary C/Cn ratio and a decrease of E/NE ratio are concomitant with alterations in mood state and performance, all these parameters being associated with physical and psychological stress.